Religious Moderation in The City Of Pancasilais: Study on the Tradition of Halal Bihalal and Christmas Together as a Cultural Basis for Religious Tolerance In Salatiga City - Faidi, Ahmad (KOMUNITAS: International Journal of Indonesian Society and Culture, 2021)
The Setara Institute (in 2018) designated Salatiga City as the number two Tolerant City in Indonesia. The culture of togetherness, as reflected in the celebration of Halal Bihalal and Christmas Together, in the midst of the multi-cultural society of the City of Salatiga is a fundamental factor in the formation of a tolerant and mutually supportive life order. This type of naturalistic qualitative research, using a critical analytical descriptive approach, makes the Pengilon hamlet community its material object. The results of this study found that religious moderation which was manifested in the celebration of halal bihalal and Christmas together, became a medium for preserving the value of tolerance that was so effective for every level of society in Salatiga City. Such a cultural base can guarantee the strength of the four indicators set by the Setara Institute, namely city government regulations; government action; social regulation; and religious demographics, in the ranking of tolerant cities in Indonesia.